PENYULUHAN TENTANG PELAYANAN CONTONUITY IF CARE (COC) ANEMIA PADA REMAJA MAHASISWA S1 KEBIDANAN UNIVERSITAS KADER BANGSA PALEMBANG - Mastina Mastina; Wahyu Ernawati (COVIT (Community Service of Health), 2023)
Adolescence (age 10-19 years) is a unique and critical period in one's life. Adolescence is a transition between childhood and adulthood marked by significant physical and psychosocial changes including risks and opportunities that affect the lives of youth perspectives. .WHO estimates that 42% of children less than 5 years of age and 40% of pregnant women worldwide experience anemia. Data on anemia for pregnant women based on Riskesdas data showed 84.6% anemia at the age of 15-24 years, 33.7% at the age of 25-34 years, 33.6% at the age of 35-44 years, and 24% at the age of 45-54 years. Counseling programs about anemia in adolescents are delivered in the form of lectures and questions and answers. The activity ran effectively, the participants enthusiastically listened and asked various things about anemia in adolescents that were not understood by the counseling participants. The purpose of this activity is to increase student knowledge about how anemia continuity of care (COC) services are provided to adolescents. The target of the activity was 83 Midwifery undergraduate students at Kader Bangsa University. This activity was carried out starting from filling out the pre test, counseling using media in the form of Power Point (PPT), filling in the post test, providing additional media in the form of posters. The activity was carried out at Kader Bangsa University Palembang. From the results of the activity, there was an increase in knowledge and understanding of Undergraduate Midwifery Students at Kader Bangsa University regarding anemia continuity of care (COC) services in adolescents. Adolescence (age 10-19 years) is a unique and critical period in one's life. Adolescence is a transition between childhood and adulthood marked by significant physical and psychosocial changes including risks and opportunities that affect the lives of youth perspectives. .WHO estimates that 42% of children less than 5 years of age and 40% of pregnant women worldwide experience anemia. Data on anemia for pregnant women based on Riskesdas data showed 84.6% anemia at the age of 15-24 years, 33.7% at the age of 25-34 years, 33.6% at the age of 35-44 years, and 24% at the age of 45-54 years. Counseling programs about anemia in adolescents are delivered in the form of lectures and questions and answers. The activity ran effectively, the participants enthusiastically listened and asked various things about anemia in adolescents that were not understood by the counseling participants. The purpose of this activity is to increase student knowledge about how anemia continuity of care (COC) services are provided to adolescents. The target of the activity was 83 Midwifery undergraduate students at Kader Bangsa University. This activity was carried out starting from filling out the pre test, counseling using media in the form of Power Point (PPT), filling in the post test, providing additional media in the form of posters. The activity was carried out at Kader Bangsa University Palembang. From the results of the activity, there was an increase in knowledge and understanding of Undergraduate Midwifery Students at Kader Bangsa University regarding anemia continuity of care (COC) services in adolescents. Keywords: Continuity of Care (COC), Adolescent Anemia, Midwifery Services